Orchidectomy enhances the effects of phenylephrine in rat isolated portal vein - Rossignoli, Patricia de Souza [UNESP]; Pereira, Oduvaldo C. M. [UNESP]; Chies, Agnaldo B. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
P>1. Orchidectomy results in long-term testosterone deprivation similar to that observed in male clinical pathologies, such as hypogonadism and age-related reductions in plasma testosterone concentrations. Although the vascular effects of these sorts of hormone deprivations are known in arteries, they have not been studied to the same extent in veins.2. The aim of the present study was to determine the effect of orchidectomy, with or without subsequent testosterone replacement (started 23 days after orchidectomy; 10 mg/kg, i.m., testosterone propionate once every 5 days for 3 weeks), on responses of rat isolated portal veins and vena cavae to exogenous phenylephrine (PE). Isolated vessels were mounted in an organ bath and concentration-response curves constructed to PE (10-10-10-4 mol/L), endothelin (ET; 10-10-10-5 mol/L) and KCl (10-2-1.2 x 10-1 mol/L; as a control).3. Orchidectomy had no effect on contractile responses of either the portal vein or vena cava to KCl. However, orchidectomy enhanced the maximum response (R(max)) of the portal vein, but not the vena cava, to PE. Testosterone replacement had no effect on these responses. The effects of orchidectomy on the R(max) to PE in portal veins were not altered by the nitric oxide synthase inhibitor NG-nitro-l-arginine methyl ester (10-4 mol/L) alone or combined with 10-5 mol/L indomethacin (a non-selective cyclo-oxygenase inhibitor), but they were abolished following treatment of isolated vessels with the ET(A) and ET(B) receptor antagonists BQ-123 and BQ-788 (both at 10-6 mol/L). Orchidectomy did not alter portal vein responses to the application of exogenous ET.4. The results of the present study indicate that orchidectomy-induced decreases in plasma testosterone can increase the venoconstrictor effects of PE on the portal vein and that this effect involves activation of both ET(A) and ET(B) receptors by locally produced ET.
Keywords: endothelin; orchidectomy; portal vein; sympathomimetic; testosterone; vena cava